Survey of Gross Motor Skills Among Grade III and IV Students at SDN 14 Balaesang - Faradila Faradilla; Didik Purwanto; Arief Aditya Rifandi; Andi Sultan Brilin Susandi Eka Wahyudi (International Journal on Advanced Science, Education, and Religion, 2026)
This study aims to determine the gross motor skill levels of third and fourth-grade students at SDN 14 Balaesang. The study employs a quantitative approach using a descriptive survey method. The research population consists of all third and fourth-grade students at SDN 14 Balaesang, totaling 47 students (21 in grade III and 26 in grade IV). A total sampling technique was used, meaning the entire population served as the research sample. The research instrument consisted of gross motor skill tests, including a one-leg standing balance test, a ball throw-and-catch test, a standing long jump test, and a 30-meter sprint test. Data were analyzed using descriptive statistics, specifically mean values, standard deviations, frequencies, and percentages. The results indicate that the students' gross motor skills regarding balance, coordination, and leg muscle strength generally fall into the "good" to "very good" categories. In grade III, balance ability was predominantly in the "very good" category (57.1%); the ball throw-and-catch test showed a relatively balanced distribution across "very good," "good," and "average" categories; and the standing long jump test was dominated by "good" (57.14%) and "very good" (42.86%) categories. However, sprint running ability remained in the "poor" and "very poor" categories. In grade IV, balance ability was predominantly "very good" (69.23%); the ball throw-and-catch test was dominated by "good" (42%) and "very good" (35%) categories; and the standing long jump test was dominated by the "very good" category (73%). Meanwhile, sprint running ability was still dominated by the "very poor" category (53.9%).